Concise Synthesis of Substituted Quinolizin‐4‐ones by Ring‐Closing Metathesis. Issue 26 (25th July 2014) - Alanine, Thomas A.; Galloway, Warren R. J. D.; McGuire, Thomas M.; Spring, David R.
Abstract: The 4 H ‐quinolizin‐4‐one scaffold is of significant pharmaceutical interest. This heterocyclic structure is predicted to have attractive physico‐chemical properties and is present in a variety of biologically active molecules. Despite these interesting characteristics, 4 H ‐quinolizin‐4‐ones are largely under‐represented in current small molecule screening libraries, and, therefore, this scaffold has been poorly investigated. Herein, a new strategy is reported for the syntheses of these rare and biologically interesting 4 H ‐quinolizin‐4‐ones. This modular route involves the regioselective N ‐alkylation of 6‐halo‐2‐pyridones followed by a Stille cross‐coupling, ring‐closing metathesis, and palladium‐catalyzed dehydrogenation reaction sequence. This method furnishes the target compounds in good yields and allows for access to unusual substitution patterns that are difficult to achieve by using other synthetic strategies. Abstract : 4 H ‐Quinolizin‐4‐ones are of significant pharmaceutical interest, yet they are infrequently explored for drug discovery because of difficulties with synthetic accessibility. A new strategy is reported for the synthesis of this rare and biologically interesting class of compounds.